The science and art of the manufacture of Portland cement with observations on some of its constructive applications - Reid, Henry (E. & F.N. Spon, 1877)
In this title the author outlines: alternative methods of cement production; cement-burning; cement-testing; the applications of concrete, particularly to paving and sewerage engineering.